2018
DOI: 10.2166/wst.2018.305
|View full text |Cite
|
Sign up to set email alerts
|

Selection of quorum quenching (QQ) bacteria for membrane biofouling control: effect of different Gram-staining QQ bacteria, Bacillus sp. T5 and Delftia sp. T6, on microbial population in membrane bioreactors

Abstract: This study aimed to address the gap in understanding how the microbial community present within quorum quenching-membrane bioreactor (QQ-MBRs) changes during the operations by investigating the behavior of two different types of QQ bacteria, Bacillus sp. T5 and Delftia sp. T6. The anti-biofouling effects of T5 and T6 in the QQ-MBR were 85% and 76%, respectively. According to the Illumina HiSeq results, when the QQ-MBR was operated with Gram-positive bacteria, T5, in the mixed liquor a reduction was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…When the microbial population reaches a certain density level, the concentration of signaling molecules reaches a threshold value. By signal transduction through related proteins, including receptor protein kinases, signals are transmitted across the cells, thus affecting the expression of specific genes and regulating the physiological characteristics of microbial populations [44][45][46]. Bacteria use quorum sensing for cell-to-cell communication and coordination of activities in the complex environment, which enables the entire bacterial population to survive [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…When the microbial population reaches a certain density level, the concentration of signaling molecules reaches a threshold value. By signal transduction through related proteins, including receptor protein kinases, signals are transmitted across the cells, thus affecting the expression of specific genes and regulating the physiological characteristics of microbial populations [44][45][46]. Bacteria use quorum sensing for cell-to-cell communication and coordination of activities in the complex environment, which enables the entire bacterial population to survive [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…into a nontoxic paint, bacterial and diatoms colonization and growth were successfully controlled by QS interference in artificial marine settings [234]. In industry, QQ is applied in wastewater treatment, where membrane bioreactors used for reclamation and desalination of brackish and seawater are constrained by biofouling of the membrane filters [235]. Fouling biofilms formed by Aeromonas hydrophila and P. putida [236] are prevented by small-signal interfering compounds added to antifouling coatings or by immobilizing QQ enzymes or marine organisms engineered to secrete QS inhibitors [237][238][239][240].…”
Section: Bacterial Communication-quorum Sensingmentioning
confidence: 99%
“…Additionally, the research concluded that the interaction of T5 concerning Gram-negative and Gram-positive bacteria was critical to MBR performance. Gül, Imer, Park, and Koyuncu (2018b) also conducted research on antifouling behavior and the associated impact on the microbial community for two different QQ species: Bacillus sp. T5 and Delftia sp.…”
Section: Quorum Quenchingmentioning
confidence: 99%
“…Gül, Imer, Park, and Koyuncu (2018b) also conducted research on antifouling behavior and the associated impact on the microbial community for two different QQ species: Bacillus sp. T5 and Delftia sp.…”
Section: Membrane Foulingmentioning
confidence: 99%